2021
DOI: 10.1101/2021.12.01.21266670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal study of DNA methylation and epigenetic clocks prior to and following test-confirmed COVID-19 and mRNA vaccination

Abstract: The host epigenetic landscape is rapidly changed during SARS-CoV-2 infection and evidence suggests that severe COVID-19 is associated with durable scars to the epigenome. Specifically, aberrant DNA methylation changes in immune cells and alterations to epigenetic clocks in blood relate to severe COVID-19. However, a longitudinal assessment of DNA methylation states and epigenetic clocks in blood from healthy individuals prior to and following test-confirmed non-hospitalized COVID-19 has not been performed. Mor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…36 Not only are the elderly up to 90-fold more vulnerable to death from COVID-19, 37 but we and others have previously reported that accelerated biological age is associated with incidence and severity of COVID-19. [38][39][40][41][42] Longitudinal biological age data covering the COVID-19 disease course is also extremely limited.…”
Section: Severe Covid-19 Causes a Reversible Increase In Biological Agementioning
confidence: 99%
“…36 Not only are the elderly up to 90-fold more vulnerable to death from COVID-19, 37 but we and others have previously reported that accelerated biological age is associated with incidence and severity of COVID-19. [38][39][40][41][42] Longitudinal biological age data covering the COVID-19 disease course is also extremely limited.…”
Section: Severe Covid-19 Causes a Reversible Increase In Biological Agementioning
confidence: 99%